Formation of Foreign Language Discursive Competence in Oral Communication (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article explores the intricate process of developing foreign language discursive competence, with a specific focus on oral communication. Discursive competence, the ability to engage in meaningful and effective communication, is a multifaceted skill that goes beyond linguistic proficiency. Through an in-depth analysis of theoretical frameworks, empirical studies, and practical applications, this article aims to shed light on the various factors influencing the formation of discursive competence in foreign language learners. The discussion encompasses language acquisition theories, socio-cultural influences, classroom methodologies, and the role of technology in shaping oral communication skills. The insights provided can inform educators, learners, and policymakers in optimizing language learning environments.